2019
DOI: 10.1111/jth.14531
|View full text |Cite
|
Sign up to set email alerts
|

Role of RXRβ in platelet function and arterial thrombosis

Abstract: Objective: Retinoid X receptors (RXR) are a family of nuclear receptors that play critical roles in the regulation of numerous fundamental biological processes including cell proliferation, differentiation, and death. Earlier studies suggested that treatment with RXR agonists attenuates platelet activation in all adults (male and femal) and mice; however, the underlying molecular mechanisms have remained insufficiently understood. To elaborate further on this issue, we characterized megakaryocyte and platelet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recent advances reveal that RXRs may exert direct beneficial effects in cardiovascular diseases via homodimerization with itself or heterodimerization with other nuclear receptors [ 4 , 5 ]. Studies have shown that novel functions of RXRs in macrophage lipid homeostasis, inflammation activation, vascular protection and platelets contribute to the protective effect of RXRs in atherosclerosis [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, most studies focused on RXRα.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances reveal that RXRs may exert direct beneficial effects in cardiovascular diseases via homodimerization with itself or heterodimerization with other nuclear receptors [ 4 , 5 ]. Studies have shown that novel functions of RXRs in macrophage lipid homeostasis, inflammation activation, vascular protection and platelets contribute to the protective effect of RXRs in atherosclerosis [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, most studies focused on RXRα.…”
Section: Introductionmentioning
confidence: 99%